2020
DOI: 10.1186/s12876-020-01550-2
|View full text |Cite
|
Sign up to set email alerts
|

Mixed adenoneuroendocrine carcinoma of the hepatic bile duct: a case report and review of the literature

Abstract: Background The World Health Organization's updated classification of digestive system neuroendocrine tumors in 2010 first proposed the classification of mixed adenoneuroendocrine carcinoma (MANEC). The incidence of biliary malignant tumors with neuroendocrine tumors accounts for less than 1% of all neuroendocrine tumors. Moreover, the incidence of hilar bile duct with MANEC is very rare. Case presentation A 65-year-old female patient came to our hospital for repeated abdominal pain for more than 4 months and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Many studies show that Corona virus is present in body fluids and blood. [ 10 , 11 , 21 24 ] Consequently, all procedures involving bone cutting/ drilling machines, unipolar and bipolar thermal cautery machines, especially in head and neck region have a high risk of infectious aerosol generation [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show that Corona virus is present in body fluids and blood. [ 10 , 11 , 21 24 ] Consequently, all procedures involving bone cutting/ drilling machines, unipolar and bipolar thermal cautery machines, especially in head and neck region have a high risk of infectious aerosol generation [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The early symptoms of CCA are not obvious, studies have shown that only about 35% of patients can be detected early and receive surgical treatment, and most of the patients have already developed advanced stages by the time of presentation. For patients who may undergo surgical treatment, we need to think about how to safely perform surgical treatments 8 . Accurate preoperative evaluation is very necessary for patients, not only can it effectively increase the success rate of surgery, but also improves the quality of life and prognosis of patients.…”
Section: Surgerymentioning
confidence: 99%
“…Coronaviruses are named for their spikey surface proteins that resemble a crown (Latin corona ); these are one of several structural proteins [ 3 , 4 ]. The SARS-CoV-2 virus is thought to enter the cell via angiotensin converting enzyme 2, a transmembrane protein in type-2 pneumocytes that are found in the alveoli, nasal goblet cells, and intestinal epithelial cells [ 2 5 ]. It is thought that the virus preferentially infects the type-2 pneumocytes in the lungs, but may concurrently infect intestinal epithelial cells [ 5 ].…”
Section: Introductionmentioning
confidence: 99%